What Does Successful Aging Mean? Lay Perception of Successful Aging Among Elderly Singaporeans. (1st March 2017) - Feng, Qiushi; Straughan, Paulin Tay
Abstract: Objectives: We explore the culturally specific meaning of successful aging in Singapore, an ethnically diverse city–state in Asia. We aim to investigate lay perceptions of successful aging among the elderly individuals in Singapore and further examine variations of these perceptions. Methods: We applied a mixed-method research design. Firstly, we conducted qualitative interviews with 49 elderly respondents, generating 12 main subjective components of successful aging. Next, we did a national survey with a sample of 1, 540 local residents aged 50 to 69 years, in which respondents were asked to evaluate the importance of each subjective component of successful aging. We used the regression models and latent class analysis to analyze the correlatives of successful aging and to classify the elderly individuals by perception types. Results: Among 12 components of successful aging, those related to self-sufficiency received the highest acknowledgment among the elderly individuals in Singapore. At least half of them simultaneously highlighted independence from family and dependence on family. Malays and Indians in Singapore valued more of the roles of spouse and children in successful aging, as compared with Chinese. The latent class analysis classified four groups of the elderly individuals according to their lay views on successful aging. Discussion: As compared with the western model of successful aging, the elderly individuals in Singapore perceived successful aging with a strong focus on familism. These lay perceptions also significantly varied among these elderly individuals.